The m6A writers regulated by the IL-6/STAT3 inflammatory pathway facilitate cancer cell stemness in cholangiocarcinoma - Hua Ye; Tianqi Chen; Zhancheng Zeng; Bo He; Qianqian Yang; Qi Pan; Yueqin Chen; Wentao Wang (Cancer Biology & Medicine, 2022)
Objective: Investigation of the regulatory mechanisms of cell stemness in cholangiocarcinoma (CCA) is essential for developing effective therapies to improve patient outcomes. The purpose of this study was to investigate the function and regulatory mechanism of m6A modifications in CCA cell stemness. Methods: Interleukin 6 (IL-6) treatment was used to induce an inflammatory response, and loss-of-function studies were conducted using mammosphere culture assays. Chromatin immunoprecipitation, polysome profiling, and methylated RNA immunoprecipitation analyses were used to identify signaling pathways. The in vitro findings were verified in a mice model. Results: We first identified that m6A writers were highly expressed in CCAs and further showed that STAT3 directly bound to the gene loci of m6A writers, showing that IL-6/STAT3 signaling regulated expressions of m6A writers. Downregulating m6A writers prevented cell proliferation and migration in vitro and suppressed CCA tumorigenesis in vivo. Notably, the knockdown of m6A writers inhibited CCA cell stemness that was triggered by IL-6 treatment. Mechanistically, IGF2BP2 was bound to CTNNB1 transcripts, significantly enhancing their stability and translation, and conferring stem-like properties. Finally, we confirmed that the combination of m6A writers, IGF2BP2, and CTNNB1 distinguished CCA tissues from normal tissues. Conclusions: Overall, this study showed that the IL-6-triggered inflammatory response facilitated the expressions of m6A writers and cell stemness in an m6A-IGF2BP2-dependent manner. Furthermore, the study showed that m6A modification was a targetable mediator of the response to inflammation factor exposure, was a potential diagnostic biomarker for CCA, and was critical to the progression of CCA.